Rice Root Nematode an emerging threat to irrigated rice - Berliner, J; Pokhare, S Somnath; Adak, Totan; Guruprasannapandi, Guruprasannapandi (Indian Farming, 2017)
The RRN are the most frequent nematode species encountered inirrigated rice ecosystem, whose population yield may range from100-600 nematode/100 CC soil. Though it is unseen and unable tocause visible symptoms, the distribution and abundance of theRRN urge the importance of systematic study to evaluate itseconomic loss, lifecycle (voltinism), pathogenic ability, adaptability and survival ability to prevent possible outbreaks.